Immediate actions on coal phaseout enable a just low-carbon transition in China's power sector. (15th February 2022) - Zhang, Xiaoli; Cui, Xueqin; Li, Bo; Hidalgo-Gonzalez, Patricia; Kammen, Daniel M; Zou, Ji; Wang, Ke
Highlights: A bottom-up job impact model is built to quantify the job impacts of decarbonization pathways of China's power sector. The net job impact of net-zero transition in China's power sector is positive. Early decarbonization and job training facilitates a socially equitable transition. Delayed mitigation action results in large mismatch of job creations and losses, hindering the ability of China to become carbon neutral by 2060. Abstract: To meet the 2060 carbon neutrality target, China will need to phase out existing coal-fired power plants by 2050 or before. The electricity supply sector directly employs over 2 million and an additional 2 million when indirect employment including product and machinery production are included. To investigate the policy options and pathways available to meet the national climate goal while transitioning this jobs-intensive and economically powerful sector, we developed a plant-level job accounting model, and combine it with a power sector optimization model to assess job loss in the coal sector, as well as job creation in the burgeoning renewable power sector in China. We find that national and provincial policy actions to support an early and managed transition help to ensure a job-rich and both geographically and socioeconomically equitable shift from coal to clean energy. Specifically, the projected decline in fossil-fuel jobs can be fully offset by job new creation in the expanding renewable energy sector. Current COVID-19 economic stimulus plans include a potential new coal boom, where China could build up to 247 GW of additional plants, and thus delay the transition by a decade or more. We find that this action would result in up to 90% of coal-fired workers losing jobs between 2030 and 2040 without a clear pathway to absorb these workers in what will be an already mature clean energy economy. Provinces with massive coal fleets and limited renewable energy resources, notably Anhui, Henan, Hebei and Shandong, etc., would face a particularly disruptive mismatch of job gains and losses.